Comparison of "My Tooth the Happiest" educational game with standard dietary counseling for preference toward non-cariogenic food items in preschool children: A Randomized control trial - Tanvi Saraf; Rahul Hegde; Preetam Shah (Wolters Kluwer Medknow Publications, 2023)
Background: A change in food preferences is difficult to bring about, thus there is a need of an innovative tool which would cater to the developing cognition of the child but at the same time be fun and engaging. Aim: To assess and compare playing "My tooth the happiest" an educational game with standard dietary counseling in preschool children for preference for noncariogenic food items. Settings and Design: Randomized controlled trial. Materials and Methods: The parents of 51 children aged between 4 and 6 years, answered a preintervention questionnaire on the daily food preferences of their children and were scored as per the scale which depicted the frequency status of dietary preferences. In Group A, 25 children played the educational game "My tooth the Happiest" and Group B of 26 children were given verbal dietary counseling. A postintervention questionnaire was answered by the parents on the 8th, 16th, and 30th days and were scored as per the scale. Statistical Analysis: The intergroup comparison of Group A and Group B was done by Mann-Whitney test and the intra-group analysis by Friedman's test. Results: The inter-group analysis showed a highly significant (P < 0.01) result at the 8th, 16th, and 30th day with lower mean scores in Group A than Group B. The intragroup analysis within both the groups showed a highly significant change (P < 0.01). Conclusions: Playing an inexpensive, fun, educational game could be a "Game changer" for dietary counseling in pediatric dentistry for preschoolers.